ENVIRONMENTAL SAFETY IMPROVEMENT OF SURFACE AND GROUND WATER CONTAMINATION AT THE AIRPORT AREA - Madzhd, Svitlana (Proceedings of National Aviation University (archive), 2016)
Purpose: Taking into account that the airport "Kyiv" is located in one of the central districts of Kyiv and does not have clearly established sanitary protection zones, the problem of environmental pollution is topical and requires monitoring and research. In order to improve environmental compliance we made assessment of superficial and ground water quality in airport zone. Methods: Water quality was estimated by the biotesting method, hydrochemical analysis, and by oil products detection method. Results We performed analysis of wastewaters of airport “Kyiv” and superficial waters of river Nyvka. The samples took place: above the airport drainage, in the drainage place and below drainage place. We conducted assessment of ground waters, which are sources of water supply, on different distance from an airport (20 m, 500 m, 1000 m, 1500 min). Results of hydrochemical investigations of river indicated excess of nitrogen compounds content compare to regulatory discharge. Thus, it was defined excess of ammonia nitrogen in wastewaters in three times and in place of dispersion – in ten times; the content of nitrite nitrogen in the river sample after discharge exceeds in 22 times norm. Analysis of drinking water in airport zone has showed extremely high level of pollution by nitrite nitrogen exceeding norm in 7-17 times. After analysis it was defined high level of river pollution by oil products (in 26-32 times higher than MPC), and ground water in 1, 5-2 times. Results of biotesting confirmed data of hydrochemical investigations of superficial water state (acute toxicity was observed in drainage area and in place of drainage dispersion). Discussion: Increased content of nitrite indicates the strengthening of decomposition process of organic matter in conditions of slower oxidation of NO into NO. This parameter is major sanitary indicator which indicates pollution of water body. High content of such specific pollutant for aviation transport processes as oil products indicates negative impact of airports on superficial and ground waters. Complex usage of hudrochemical and biotesting methods has increased accuracy of assessment. So, the most effective method for assessment of possible hazard of some sources for water flora and fauna is biotesting, which is based on registration of test objects reactions.